EVALUATION OF CRUDE FLAXSEED (Linum usitatissimum L.) OIL IN BURN WOUND HEALING IN NEW ZEALAND RABBITS - Beroual, Katiba; Agabou, Amir; Abdeldjelil, Mohamed-Cherif; Boutaghane, Naima; Haouam, Saïd; Hamdi-Pacha, Youcef (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Burns are among the most prevalent injuries in humans with high cost in health care and heavyprolonged or permanent physical, psychological and social consequences. Commercial antimicrobial creams anddressing agents are unsuccessful in healing deep burn wounds.Materials and Methods: A study was conducted to assess the impact of crude linseed oil (LSO) topical application onburn wounds healing in rabbits in comparison with untreated wounds (NAT) and those treated with Vaseline gel(VAG) and Cicatryl-Bio ointment (CBO). By the 28th day post burning, skin biopsies were analyzed for histologicaland cytological lesions. The presence of various bioactive phytochemical groups in linseed was also screened.Results: Phytochemical screening has resulted in high concentrations of flavonoids and terpenoids, low amounts ofcatechic tannins and total absence of alkaloids and saponosides. All along the trial, the rate of wounds contraction wasfound to be significantly higher in burns treated with LSO which had also a significant shorter healing period (26±5.89days) as compared to the other treatments. LSO healed wounds included less inflammatory cells, complete epitheliumregeneration with a reduced thickness of the new formed dermis, discreet fibrosis, enhanced neo-vascularization,increased number of collagen fibers, fibroblasts and many myofibroblasts. Additionally, no adverse effects of LSO oncicatrization process were recorded.Conclusion: These findings prove the safety and efficaciousness of linseed oil topical application in the therapy ofburn wounds.